New Brazilian Predaceous Midges of the Genus Monohelea-Kieffer, and Redescription of M-Guaimiesi (Diptera, Ceratopogonidae) - Felippebauer, María Luiza (1991)
Fil: Felippebauer, María Luiza. Instituto Oswaldo Cruz. Departamento de Entomología. Río de Janeiro; Brazil